Teaching Speaking Through Substitution Drill Technique - Tenny Murtiningsih; Nanda Oetari Triana. P (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2018)
This study presents the description how to teach speaking through substitution drill technique. It uses qualitative description method. Speaking is as one of productive skills that needs to be improved. Through speaking, we can communicate each other and express our ideas. Even speaking is important in communication but learning how to speak fluently and correctly still seems to be difficult for students. Speaking still becomes a problem for the students at the class. There are some factors that make speaking becomes a problem to produce, for example lack of self confidence, lack of vocabularies and grammar knowledge. To answer this problem, the researcher suggests to use substitution drill technique at teaching speaking. Substitution drill is one of the techniques in speaking. In this technique, the researcher drilled the students by applying some key words in the model of the dialogue given. In this research, the researcher invited 14 students from the first semester of Bilingual Nursing Program in a private university in Banjarmasin as the subject of the research. The researcher did the research by observing the class activity, interviewed them and administering questionnaires to the subjects above.